Proof-of-concept Studies for siRNA-mediated Gene Silencing for Coagulation Factors in Rat and Rabbit - Zhu Chen; Bin Luo; Tian-Quan Cai; Anil Thankappan; Yiming Xu; Weizhen Wu; Jillian DiMuzio; Traci Lifsted; Marty DiPietro; Jyoti Disa; Bruce Ng; Karen Leander; et al. (Molecular Therapy: Nucleic Acids, 2015)
The present study aimed at establishing feasibility of delivering short interfering RNA (siRNA) to target the coagulation cascade in rat and rabbit, two commonly used species for studying thrombosis and hemostasis. siRNAs that produced over 90% mRNA knockdown of rat plasma prekallikrein and rabbit Factor X (FX) were identified from in vitro screens. An ionizable amino lipid based lipid nanoparticle (LNP) formulation for siRNA in vivo delivery was characterized as tolerable and exerting no appreciable effect on coagulability at day 7 postdosing in both species. Both prekallikrein siRNA-LNP and FX siRNA-LNP resulted in dose-dependent and selective knockdown of target gene mRNA in the liver with maximum reduction of over 90% on day 7 following a single dose of siRNA-LNP. Knockdown of plasma prekallikrein was associated with modest clot weight reduction in the rat arteriovenous shunt thrombosis model and no increase in the cuticle bleeding time. Knockdown of FX in the rabbit was accompanied with prolongation in ex vivo clotting times. Results fit the expectations with both targets and demonstrate for the first time, the feasibility of targeting coagulation factors in rat, and, more broadly, targeting a gene of interest in rabbit, via systemic delivery of ionizable LNP formulated siRNA.